Involvement of retrovirus reverse transcriptase-associated RNase H in the initiation of strong-stop (+) DNA synthesis and the generation of the long terminal repeat. - Resnick, R (1984)
Reconstructed enzymatic reactions containing purified reverse transcriptase and defined analog substrates which mimic those purported to be natural substances for reverse transcription in vivo were employed to delineate the mechanism of strong-stop (+) DNA synthesis. Our analysis of this system has indicated that strong-stop (+) DNA synthesis is initiated after the introduction of a nick in the viral RNA genome between a polypurine sequence and an inverted repeat that represents the end of the long terminal repeat. Since inhibitors of the reverse transcriptase-associated RNase H activity prevent the introduction of the nick and the synthesis of strong-stop (+) DNA synthesis, it appears that this particular reverse transcriptase-associated enzymatic activity is responsible for the initiation of strong-stop (+) DNA. Our data also indicated that the RNase H activity creates a second nick in the viral RNA genome 11 nucleotides upstream from the strong-stop (+) DNA initiation site since the strong-stop (+) DNA synthesized in these reactions is covalently linked to an oligoribonucleotide 11 residues in length. Nucleotide sequence analysis of the oligoribonucleotide primer molecule indicated that a single homogenous oligomer was associated with strong-stop (+) DNA exhibiting the sequence rArGrGrGrArGrGrGrGrGrA. The oligoribonucleotide primer can be removed from strong-stop (+) DNA by the purified reverse transcriptase, which creates a nick at the junction between the primer and strong-stop (+) DNA. These data demonstrate that the initiation of strong-stop (+) DNA synthesis is mediated by RNase H and that the site of initiation is exactly at the end of the long terminal repeat, providing evidence for yet another function of this reverse transcriptase-associated enzymatic activity in the synthesis of retrovirus DNA.